1995
DOI: 10.1159/000126833
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Anti-Prolactin Receptor Antibodies on Prolactin Binding in Brain and Prolactin-Induced Feeding Behavior in Ring Doves

Abstract: Although binding sites for prolactin (PRL) have been mapped and partially characterized in the brains of several species, there is as yet no direct evidence that the effects of intracranial PRL on brain function are receptor-mediated events. We addressed this question by testing whether antibodies generated against rat liver PRL receptors can effectively antagonize the ability of PRL to enhance feeding behavior in male ring doves (Streptopelia risoria). Both agents were administered directly to the ventromedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…2 B). Several studies addressing behavioral effects of PRL have also demonstrated PRL actions in both genders (Li et al, 1995;Heil, 1999). PRL-R have been mapped in the brain of both female (Crumeyrolle-Arias et al, 1993;Chiu and Wise, 1994;Bakowska and Morrell, 1997;Grattan, 1998, 1999) and male rats (Muccioli et al, 1991;Roky et al, 1996;Pi and Grattan, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 B). Several studies addressing behavioral effects of PRL have also demonstrated PRL actions in both genders (Li et al, 1995;Heil, 1999). PRL-R have been mapped in the brain of both female (Crumeyrolle-Arias et al, 1993;Chiu and Wise, 1994;Bakowska and Morrell, 1997;Grattan, 1998, 1999) and male rats (Muccioli et al, 1991;Roky et al, 1996;Pi and Grattan, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of different techniques, this neuropeptide has been shown to participate in the regulation of maternal behavior (Bridges et al, 1990;Lucas et al, 1998), grooming (Drago et al, 1983), and food intake in mammalian (Noel and Woodside, 1993) and nonmammalian species (Li et al, 1995). A possible involvement of PRL in stress response mechanisms is suggested by the findings that (1) PRL is released into the blood from pituitary lactotroph cells in response to exposure to different stressors (Neill, 1970;Seggie and Brown, 1975), (2) chronic stress induced the expression of the long form of the PRL receptors (PRL-R) in choroid plexus cells (Fujikawa et al, 1995), and (3) administration of PRL into the cerebral ventricles prevented the stressinduced formation of gastric ulcers and showed antidepressant effects during forced swimming (Drago et al, 1985(Drago et al, , 1990.…”
mentioning
confidence: 99%
“…Therefore, the increased expression of PRL receptor in the VMH was probably not initiated during pregnancy but caused by suckling during lactation. PRL receptors in the VMH have been demonstrated to be involved in control of feeding behavior [36]. Markedly increased food intake is characteristic for lactating mothers to meet nutritional demands.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, some suggestions can be made. It is suggested that the VMH regulates feeding behaviour (Li et al 1995). Since experimental hyperprolactinaemia produces an increase in food intake in female rats (Sauve & Woodside 1996), PRL-R in the VMH may be involved in the increased feeding behaviour specific to lactating rats.…”
Section: Discussionmentioning
confidence: 99%